Teaching astronomy to Fundamental Education students: an investigation on the Universe (Research, Society and Development, 2020)
The article consists of a report of teaching experience about the elaboration and application of a didactic proposal for the teaching of Astronomy to students of sixth year of elementary school. the activities were developed by students of the "Conhecendo a Escola" project of UFPR’s Licenciar program. This proposal comprises eleven classes and is attended by eighteen students. Its objectives were: to provide an understanding of the basic concepts related to astronomy; analyze how didactic actions carried out in the course of the pedagogical workshops carried out during the application of the pre-test and in the post-test and investigate the previous knowledge that the students about this theme.  The themes are: the solar system; the movements of rotation, translation and revolution carried out by the Earth and the Moon; the formation of the seasons and eclipses. The pedagogical workshops were the object of analysis of the theoretical-practical experiences, based on the social interaction between the teacher, students and didactic resources: videos, slides and simulators, making scale models of the solar system, elaboration of a game and experiments. As a theoretical framework, we used the Theory of Meaningful Learning, the Three Pedagogical Moments and Peer Instruction. Regarding the results obtained, we verified that students have a high percentage of correct answers in the post-test questions, which are composed of questions from the Brazilian Astronomy Olympics (BAO). Finally, as a final result, it considers that the theoretical pillars and the proposed sequence of activities were efficient to teaching and learning process of basic concepts of astronomy.